2022
DOI: 10.3389/fonc.2022.913432
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multi-Omics Data Analysis Reveals Associations Between Glycosylation and Stemness in Hepatocellular Carcinoma

Abstract: BackgroundGlycosylation plays an essential role in driving the progression and treatment resistance of hepatocellular carcinoma (HCC). However, its function in regulating the acquisition and maintenance of the cancer stemness-like phenotype in HCC remains largely unknown. There is also very little known about how CAD and other potential glycosylation regulators may influence stemness. This study explores the relationship between glycosylation and stemness in HCC.MethodsGene set variance analysis (GSVA) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The results showed that the ECM-related signature was more accurate and robust than the stemness-related signature (p < 0.0001, Figure 2I). Also, the performance of the ECM-related signature was also better than other published stemness-related signatures (p < 0.0001, Figure 2J) (Zhang et al, 2020;Hong et al, 2021;Shen et al, 2021;Chen et al, 2022;Liu et al, 2022). We further explored the correlation between our prognostic model and ECM collagen or non-collagen genes.…”
Section: Construction Of the Ecm-related Prognostic Modelmentioning
confidence: 88%
“…The results showed that the ECM-related signature was more accurate and robust than the stemness-related signature (p < 0.0001, Figure 2I). Also, the performance of the ECM-related signature was also better than other published stemness-related signatures (p < 0.0001, Figure 2J) (Zhang et al, 2020;Hong et al, 2021;Shen et al, 2021;Chen et al, 2022;Liu et al, 2022). We further explored the correlation between our prognostic model and ECM collagen or non-collagen genes.…”
Section: Construction Of the Ecm-related Prognostic Modelmentioning
confidence: 88%
“…Whether a marked reduction in the CD4/CD8 ratio in SHLH patients is either governed by preferential apoptosis of CD4 T cells or excessive proliferation of activated CD8 T cells which is often reported in HLH patients; or both, needs further investigation. A number of studies have clearly demonstrated expansion of activated T cell population as a characteristic feature in HLH patients; more evidently in CD8 T cells 10,12,14 while in sepsis, suppressive T cell phenotypes or function was noticed 17,[19][20][21] . More recently, the diagnostic utility of CD38hi HLADR + activated T cells has also been reported in distinguishing active HLH from early sepsis in children 10 (Chaturvedi et al).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the remaining genes within the set of signature genes, carbamoyl phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase (CAD) play a crucial role as they encode CAD. These enzymes are essential for pyrimidine synthesis, new pyrimidine nucleotides, protein glycosylation, and the biosynthesis of phospholipids in mammals [ 38 , 39 ]. CAD is responsible for initiating the di-(UDP)-dependent glycosylation process, resulting in the production of UDP.…”
Section: Discussionmentioning
confidence: 99%